Seroprevalence of Coxiella burnetii among ewes and associated risk factors in Constantine (Northeastern Algeria) - HIRECHE, S.; AGABOU, A.; BOUAZIZ Ο. (Journal of the Hellenic Veterinary Medical Society, 2020)
Q fever is a zoonotic disease caused by the rickettsia-like Coxiella burnetii and leads to abortions and decreased reproductive performances in domestic ruminants. A serological survey, using ELISA test, was conducted to assess the prevalence of this infection in 226 ewes belonging to 39 flocks localized in Constantine (North-eastern Algeria). A pretested questionnaire has been submitted to farmers/shepherds to collect information related to relevant risk factors. Results revealed the presence of C. burnetii antibodies in 12.4% (95% CI: 8.08%−16.72%) of individual animals while 35.9% (95% CI: 21.20%−52.82%) of sampled flocks accounted at least one seropositive ewe. Significant causative associations were observed for origin of animals (χ2=14.29, P=0.001), vaccination against enterotoxaemia (χ2=12.12, P=0.002) and pox (χ2=5.30, P=0.025), access to the farm by foreign visitors (χ2=10.87, P=0.004), farmers/shepherds’ visits to other farms (χ2=6.31, P=0.021), disinfection frequency (χ2=7.98, P=0.046), pest infestation within farms (χ2=9.55, P=0.049) and abortion history (χ2=5.54, P=0.029). This recorded prevalence of Coxiella infection would indicate a possible responsibility of this agent in causing abortion and reproductive failures in the tested flocks. Implementing active surveillance programs and further investigations using more accurate analyses and including large samples of more animal species from several provinces are needed to eluci date the real occurrence and dynamics of this infection in the national livestock.